2005
DOI: 10.1097/00019501-200508000-00006
|View full text |Cite
|
Sign up to set email alerts
|

The impact of admission C-reactive protein levels on the development of poor myocardial perfusion after primary percutaneous intervention in patients with acute myocardial infarction

Abstract: On admission, high CRP level in patients with acute MI undergoing primary PCI is likely to be in the causal pathway leading to the development of poor myocardial perfusion, especially when combined with prolonged pain to balloon time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 23 publications
1
21
0
2
Order By: Relevance
“…The CRP was predictive of adverse cardiovascular outcome. 26 Schoos et al indicated that preprocedure hsCRP predicts outcome after p-PCI in patients with STEMI. 27 Delhaye et al showed that preprocedural high hsCRP levels before coronary stent implantation were associated with the risk of death or MI but are not related to stent-related complications.…”
Section: Discussionmentioning
confidence: 99%
“…The CRP was predictive of adverse cardiovascular outcome. 26 Schoos et al indicated that preprocedure hsCRP predicts outcome after p-PCI in patients with STEMI. 27 Delhaye et al showed that preprocedural high hsCRP levels before coronary stent implantation were associated with the risk of death or MI but are not related to stent-related complications.…”
Section: Discussionmentioning
confidence: 99%
“…In the recently published article we demonstrated that high CRP levels on admission in patients with AMI undergoing primary PCI is likely to be in the causal pathway leading to the development of poor myocardial perfusion, especially when combined with prolonged pain to balloon time [15]. In that study, the study population consisted of 75 patients (62 men, mean age = 61.6 ± 6.78 years), admitted to our hospital with acute anterior MI and underwent primary PCI in the left anterior descending coronary artery.…”
mentioning
confidence: 99%
“…In the recently published article we aimed to investigate the impact of CRP levels on the development of poor myocardial perfusion after PCI in patients with AMI [9]. In our study, study population consisted of 75 patients admitted to our hospital with acute anterior MI and underwent primary PCI in the left anterior descending coronary artery.…”
mentioning
confidence: 99%
“…Inflammation is a pathogenetic mechanism of endothelial dysfunction, and previous studies found a significant association between serum levels of CRP and microvascular endothelial dysfunction in several clinical contexts [6][7][8]. Accordingly, experimental studies showed that animals pre-treated with an inflammatory stimulus, resulting in raised CRP levels, had bigger infarcts, compared to controls, likely related to an impairment of effective myocardial revascularization [9].…”
mentioning
confidence: 99%